(untitled) (Web of Teachers: Inderscience Research, 2025)
Education is the process of transferring to others the lessons and intellectual potential that each person has acquired in the process of living in life. The concept of educational work outside the classroom and out of school emphasizes the need to improve educational activities, especially: the changing political system, the formation of new economic relations, the need to develop new principles, ideas, work methods that meet the demands of the time in improving educational work, and the need to rebuild the creative activity of the teacher.